Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
x²(x+3) = 25(x+3)
divide both sides by (x+3)
x² = 25
subtract 25 from both sides
x² - 25
(x+5)(x-5)
x = { -5, 5 }
divide both sides by (x+3)
x² = 25
subtract 25 from both sides
x² - 25
(x+5)(x-5)
x = { -5, 5 }
x³ + 3x² = 25x + 75
x³ + 3x² - 25x - 75 = 0
x²(x + 3) - 25(x + 3) = 0
(x² - 25) * (x + 3) = 0
(x² - 25) = 0 (x + 3) = 0
x² = 25 x = -3
x = ±5
Hope this helps! :)
x³ + 3x² - 25x - 75 = 0
x²(x + 3) - 25(x + 3) = 0
(x² - 25) * (x + 3) = 0
(x² - 25) = 0 (x + 3) = 0
x² = 25 x = -3
x = ±5
Hope this helps! :)
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.